OPINI AUDITOR SEBAGAI PEMODERASI PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PERBANKAN TAHUN 2015 – 2017 - Dian Syifaul Choirun Nisa; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTResearch which test the relationship of good corporate governance to firm value show inconsistent results. Besides there are still few research who use audit opinion as a variable that affects the value of the company. This study provides the auditor's opinion about the moderate impact of good corporate governance on the value of banking companies in 2015-2017. This study uses data analysis to conduct an overall sample survey of 43 banking companies listed on the Indonesia Stock Exchange. Observations for the period 2015-2017, with a total of 129 samples. This finding confirms that institutional ownership, independent committees and audit committees have a positive impact on company value. Although the results of research on good corporate governance by management ownership agents do not affect the value of the company. The auditor's opinion as a moderator of good corporate governance shows the positive impact of corporate governance on the value of the company. Keywords: good corporate governance, the auditor’s opinion, the value of the company.